When human cancer goes neural - Nürnberg, Christina; Heuer, Sophie; Winkler, Frank (Cancer cell, 2025)
Invasion along nerves is prognostically detrimental in pancreatic and other cancers, yet its microenvironmental composition in humans remains poorly understood. In this issue of Cancer Cell, Chen et al. present a patient-derived high-resolution spatial and molecular atlas to reveal significant effects of cancer cell invasion on neuro-immuno-oncological and other nerve features.
Gesehen am 26.01.2026